Efficient Heterogeneous Palladium‐Catalyzed Oxidative Cascade Reactions of Enallenols to Furan and Oxaborole Derivatives. Issue 5 (13th December 2019) - Li, Man‐Bo; Posevins, Daniels; Geoffroy, Antoine; Zhu, Can; Bäckvall, Jan‐E.
Abstract: A heterogeneous palladium‐catalyzed oxidative cyclization of enallenols has been developed for the construction of highly substituted furan and oxaborole derivatives. The heterogeneous catalyst (Pd‐AmP‐MCF) exhibits high activity, high site‐ and stereoselectivity, and efficient palladium recyclability in the transformations. Abstract : Heterogeneous ligand : A highly efficient heterogeneous palladium‐catalyzed oxidative cyclization of enallenols is developed here for the construction of highly substituted furan and oxaborole derivatives. The support (AmP‐MCF) of the heterogeneous catalyst (Pd‐AmP‐MCF) protect Pd species from aggregating to Pd black during the catalytic cycle, which leads to the high Pd efficiency of Pd‐AmP‐MCF.